The Values of Character Education in The Novel “Selamat Tinggal” by Tere Liye - Safitri, Diah Indri; Jaya, Wayan Satria; Marcela, Eny Dwi (IJLHE: International Journal of Language, Humanities, and Education, 2021)
The purpose of this study was to analyze the values ​​of character education in the novel “ Selamat Tinggal” by Tere Liye. The researcher cites data in the form of words, sentences, paragraphs and dialogues contained in the novel that contains various character education values ​​including: character education values ​​for reading, tolerance, working hard, appreciating achievement, honesty, love for the homeland, curiosity, environmental care, and social care. The approach used in this research is to use a qualitative method approach. With this type of library research, namely by analyzing data in the form of sentences, paragraphs, or dialogues that contain character education values. draw the final conclusion, the researcher did not use statistical formulas and hypothesis testing. Based on the results of the study, it can be concluded that the ten values ​​of character education contained in the novel Selamat Tinggal by Tere Liye that most dominantly appear are the value of character education respecting achievement. The value of character education respecting achievement is also in accordance with the title of Tere Liye's novel Selamat Tinggal, which very nicely presents the phenomenon of this product through Sintong Stay's glasses. Tere Liye seemed to express all opinions and criticisms, especially on pirated books because many of his books were also pirated.